2018
DOI: 10.1097/md.0000000000011703
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic hepatectomy for elderly patients

Abstract: Background:As the general population continues to age, there is an increase need for surgical management of elderly patients. Compared to open hepatectomy (OH), laparoscopic hepatectomy (LH) offers earlier mobilization, less blood loss, and shorter postoperative hospital stay. However, whether these advantages of LH over OH are retained in elderly patients remains to be clarified. Therefore, in this study, we sought to evaluate the feasibility, safety, and potential benefits of LH for elderly patients.Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 40 publications
2
8
3
1
Order By: Relevance
“…Interestingly, DFS in the LLR group was better than that in the OLR group even after matching. A previous study showed that worse basic disease conditions and ASA grades predicted poor clinical outcomes [15]; however, those factors had little effect on HCC recurrence or overall survival in our study. We did not identify a significant difference in the survival rate between the OLR and LLR groups.…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…Interestingly, DFS in the LLR group was better than that in the OLR group even after matching. A previous study showed that worse basic disease conditions and ASA grades predicted poor clinical outcomes [15]; however, those factors had little effect on HCC recurrence or overall survival in our study. We did not identify a significant difference in the survival rate between the OLR and LLR groups.…”
Section: Discussioncontrasting
confidence: 76%
“…Our elderly patients had a 90-day postoperative mortality rate of less than 1%, which could be associated with the decreased blood loss and decreased surgical wall trauma that occurs with the laparoscopic approach. Previous studies reported that liver resection in the elderly via the open approach had a very high mortality rate ranging from 3.5 to 5.6% [15]. Although the difference in the rate of 90-day postoperative mortality between LLR and OLR was not statistically significant, we did identify a trend favoring LLR, which we attribute to its smaller surgical incision, which would reduce exposure to bacteria and thereby decrease incisional complications.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…A 2019 meta-analysis showed that postoperative morbidity and mortality increased with age [65]. However, a 2018 meta-analysis showed that laparoscopic hepatectomy is a feasible and safe alternative to open hepatectomy in elderly patients because of the lower rates of morbidity and favorable postoperative recovery and outcomes [66]. Another 2018 meta-analysis showed that the outcomes of laparoscopic gastrectomy for elderly gastric cancer patients were comparable to those in nonelderly patients.…”
Section: Anesthesia In Elderly Patientsmentioning
confidence: 99%
“…As the development of laparoscopic technology and the update of laparoscopic instruments, laparoscopic hepatectomy is considered to be a more favorable option for the treatment of hepatolithiasis compared with open hepatectomy ( 1 ). Compared to conventional open approaches, the laparoscopic approach has been shown to cause reduced intraoperative blood loss, fewer post-operative complications, a shorter hospital stay and a shorter intestinal function recovery time, even in elderly patients ( 2 ). However, for surgeons, a high infective complication rate in elderly patients is still a substantial challenge, even when using minimally invasive techniques such as laparoscopic hepatectomy, which results in mild trauma to patients ( 3 ).…”
Section: Introductionmentioning
confidence: 99%